PENGARUH VIDEO ANIMASI TUBUHKU MILIKKU TERHADAP PENGENALAN PENDIDIKAN SEKS DI TK DARUL FALAH PADANG - Cahaya Zoja, Chinta; Hazizah, Nur; Marlina, Serli; Muthie, Imam; Syafnita, Tisna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Early childhood sexuality education is important to help children learn about their bodies, understand personal boundaries, and develop self-protection skills. However, its implementation still faces obstacles, particularly the limited availability of engaging and developmentally appropriate learning media. This study aims to analyze the effect of the animated video "My Body is Mine" on the introduction of sexuality education to early childhood students at Darul Falah Kindergarten, Padang. The study used a quantitative approach with a quasi experimental design (pre-test and post-test control group). The sample consisted of 24 children divided into experimental and control classes. Data were collected through structured observation and analyzed using normality and homogeneity tests, as well as independent sample t-tests. The results showed a significant increase in the experimental class, with a post-test average of 24.08 compared to the control class of 21.83. The hypothesis test showed a Sig. (2-tailed) value of 0.003 < 0.05, indicating a significant effect of the use of animated videos on the introduction of children's sexuality education. This finding suggests that the increase occurred because the animated video presented material in a visual, concrete, and engaging manner, making it easier for children to understand the concepts of the body, personal boundaries, and self-protection. The novelty of this research lies in the use of the contextual animated video "My Body is Mine," designed to suit the characteristics of young children, making it more effective than conventional methods. Therefore, this medium can be an innovative alternative in early childhood sexual education.